Nazi film melodrama - Heins, Laura (University of Illinois Press, 2013)
Cultural productions in the Third Reich often served explicit propaganda functions of legitimating racism and glorifying war and militarism. Likewise, the proliferation of domestic and romance films in Nazi Germany also represented an ideological stance. Rather than reinforcing traditional gender role divisions and the status quo of the nuclear family, these films were much more permissive about desire and sexuality than previously assumed. Focusing on German romance films, domestic melodramas, and home front films from 1933 to 1945, this book shows how melodramatic elements in Nazi cinema functioned as part of a project to move affect, body, and desire beyond the confines of bourgeois culture and participate in a curious modernization of sexuality engineered to advance the imperialist goals of the Third Reich. -- Publisher website.